The Right Inferior Frontal Gyrus Plays an Important Role in Unconscious Information Processing: Activation Likelihood Estimation Analysis Based on Functional Magnetic Resonance Imaging - Shi, Jilong; Huang, Haojie; Jiang, Ruichen; Mao, Xuechen; Huang, Qin; Li, Anmin (Frontiers in Neuroscience, 2022)
Unconsciousness is a kind of brain activity that occurs below the level of consciousness, and the masked priming paradigm is a classic paradigm to study unconscious perceptual processing. With the deepening of unconscious perception research, different researchers mostly use different experimental materials and different masked priming paradigms in a single experiment but not for the comprehensive analysis of the unconscious information processing mechanism itself. Thus, the purpose of this study is to conduct a comprehensive analysis through a cross-experimental paradigm, cross-experimental materials, and cross-experimental purposes. We used activation likelihood estimation to test functional magnetic resonance imaging studies, including 124 foci in 8 studies representing direct comparison of unconscious processing with baseline and 115 foci in 10 studies representing direct comparison of unconscious priming effects. In the comparison of unconscious processing and baseline, clusters formed in the left superior parietal gyrus, the right insular gyrus, and the right inferior frontal gyrus (IFG) triangular part after correcting for familywise error (FWE). In the comparison of priming effects, clusters formed in only the right IFG triangular part after correcting for FWE. Here, we found that ventral and dorsal pathways jointly regulate unconscious perceptual processes, but only the ventral pathway is involved in the regulation of unconscious priming effects. The IFG triangular part is involved in the regulation of unconscious perceptual processing and unconscious priming effects and may be an important brain area in unconscious information processing. These preliminary data provide conditions for further study of the neural correlation of unconscious information processing.